2017
DOI: 10.1177/0033354916688269
|View full text |Cite
|
Sign up to set email alerts
|

Economic Disparities and Syphilis Incidence in Massachusetts, 2001-2013

Abstract: Census tract poverty analyses can inform the targeting of interventions that make progress toward reducing disparities in rates of syphilis incidence possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Previous studies have shown that the incidence of P&S syphilis is affected by certain sociodemographic factors [ 11 12 ]. The size and structure of a population and the health care resources per capita are closely related to syphilis incidence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the incidence of P&S syphilis is affected by certain sociodemographic factors [ 11 12 ]. The size and structure of a population and the health care resources per capita are closely related to syphilis incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding socioeconomic factors, studies presented conflicting results concerning incidence. Research conducted in high-income regions, such as the United States and Europe, have shown that syphilis is more prevalent in poor areas [ 12 , 15 ]. However, contradictory conclusions have been reported in studies from middle-income and low-income countries, including China, indicating that more prosperous areas have a higher risk of syphilis [ 16 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 Prior work has examined age disparities stratified by race and sex 5 ; the distribution of cases across states, race and ethnicity, and age groups 6 ; and relationships between incidence and socioeconomic factors. 7 National estimates of US incidence, prevalence, and direct medical costs of P&S syphilis were recently updated. [8][9][10] However, there is limited information on variation in racial and ethnic disparities by both age group and region.…”
mentioning
confidence: 99%
“…Variations in P&S syphilis by US region, age group, and race and ethnicity are well documented 1 . Prior work has examined age disparities stratified by race and sex 5 ; the distribution of cases across states, race and ethnicity, and age groups 6 ; and relationships between incidence and socioeconomic factors 7 . National estimates of US incidence, prevalence, and direct medical costs of P&S syphilis were recently updated 8–10 .…”
mentioning
confidence: 99%
“…From the perspective of associated meteorological or socio-economic factors, previous studies have shown inconsistent results concerning associated factors of syphilis incidence. For example, Smock et al [ 17 ] found that syphilis incidence was higher in poverty-level groupings. However, Read et al [ 18 ] showed that economically developed areas had a higher risk of syphilis.…”
Section: Introductionmentioning
confidence: 99%